Rapid evidence profile #30.2: What are the biggest gaps in evidence about the impacts of climate change on population health in Canada, and adaptation and mitigation strategies that are applicable to Canada? - Velez, CM; Waddell, K; Berrang-Ford, L; Callaghan, M; Minx, J; Harper, S; Lavis, JN; Wilson, MG (My University, 2022)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the biggest gaps in evidence about the impacts of climate change on population health in Canada, and adaptation and mitigation strategies that are applicable to Canada in response to a decision-maker’s request.
Keywords: gaps; impacts; climate change; health; Canada; strategies